CITRA WANITA ARAB DAN EROPA DALAM NOVEL 'ILLA FATIMAH' KARYA ANIS MANSOUR: KRITIK SASTRA FEMINIS - Hermawati Putri Dian Insani (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
This study examined the images of Arabian and European women in the novel Illa Fatimah written by Anis Mansour. To describe the women's images, this study applied Â structural analysis method and ideologist feminism literature criticism approaches. It as intended to Â reveal the female characters and stereotypes in the novel The method of this research was descriptive-qualitative since the data of this study were textual in the forms of words, phrases, clauses, sentences showing the intrinsic and extrinsic elements of the novel. The result of this study showsthat there are some differences between Arabian and European woman images both in physical and psychological aspects as well as in their families and communities.